Income and education predict elevated depressive symptoms in the general population: results from the Gutenberg health study - Jasmin Schlax; Claus Jünger; Manfred E. Beutel; Thomas Münzel; Norbert Pfeiffer; Philipp Wild; Maria Blettner; Jasmin Ghaemi Kerahrodi; Jörg Wiltink; Matthias Michal (BMC, 2019)
Abstract Background Socioeconomic status (SES) has a strong association with depression or physical and mental health in general. However, as SES is a multifaceted construct these associations are not easy to explain. Further, there are several indicators and many studies only investigating two or less indicators at the same time. Therefore, this study aims to analyze the cross-sectional and longitudinal association of three defined SES dimensions (education, occupational position and household net-income) with the occurrence of elevated symptoms of depression relative to the impact of important covariates. Methods The study included observational data from 12,484 participants of the Gutenberg Health Study. The outcome was "elevated depressive symptoms" as defined by Patient Health Questionnaire (PHQ-2) ≥ 2 at the 2.5-year follow-up. Regression coefficients were adjusted for baseline covariates (age, sex, partnership, depression, anxiety, medical history of depressive or anxiety disorder and major medical diseases (MMD)) in addition to SES sum score and the three single indicators. We further examined interaction terms of the SES with sex, partnership and major medical diseases. We analyzed the sample stratified by elevated depressive symptoms at baseline, as we expected different trajectories in both subgroups. Results SES, education and household net-income were lower in the group of persons with PHQ-2 ≥ 2 at baseline, and they predicted the occurrence of PHQ-2 ≥ 2 at 2.5 year follow-up in the group of persons without elevated depressive symptoms at baseline after multivariable adjustment (SES: Odds Ratio (OR) 0.96, 0.95-0.98, p <  0.0001; education: OR 0.96, 0.93-0.99, p = 0.036; household net-income: OR 0.96, 0.92-0.99, p = 0.046) but not in the group of persons with elevated depressive symptoms at baseline. Further, we found that the impact of major medical diseases on the development of elevated depressive symptoms was buffered by high income. In addition, living in a partnership buffered the impact of a low occupational position. Conclusions Regarding the SES, the dimensions education and household net-income seem to play the most important role for socioeconomic inequalities in persons in Mid-West Germany with depressive symptoms. Trial registration Reference no. 837.020.07; original vote: 22.3.2007, latest update: 20.10.2015